Abiotic Raw-Materials in Life Cycle Impact Assessments: An Emerging Consensus across Disciplines - Drielsma, Johannes; Allington, Ruth; Brady, Thomas; Guinée, Jeroen; Hammarstrom, Jane; Hummen, Torsten; Russell-Vaccari, Andrea; Schneider, Laura; Sonnemann, Guido; Weihed, Pär (Resources (Basel), 2016)
This paper captures some of the emerging consensus points that came out of the workshop “Mineral Resources in Life Cycle Impact Assessment: Mapping the path forward”, held at the Natural History Museum London on 14 October 2015: that current practices rely in many instances on obsolete data, often confuse resource depletion with impacts on resource availability, which can therefore provide inconsistent decision support and lead to misguided claims about environmental performance. Participants agreed it would be helpful to clarify which models estimate depletion and which estimate availability, so that results can be correctly reported in the most appropriate framework. Most participants suggested that resource availability will be more meaningfully addressed within a comprehensive Life Cycle Sustainability Assessment framework rather than limited to an environmental Life Cycle Assessment or Footprint. Presentations from each of the authors are available for download [1].